Pengaruh Strategi Pembelajaran dengan Webquest Dan E kasi Diri Terhadap Peningkatan Literasi Pengetahuan - M Yusuf T (JTP - Jurnal Teknologi Pendidikan, 2015)
The objective of the research was to nd out the effects of elaboration instruction- al strategies toward student’s knowledge literacy. This research done by treatment by level design 2 x 2 conducted to 40 students at Alauddin Islamic State University of Makassar. The results found: (1) knowledge literacy students who learned with webquest are higher than without webquest: (2) there was an interaction effect between webquest usage and self-ef - cacy into student’s knowledge literacy; (3) on the group with higher level self-ef cacy, stu- dent’s knowledge literacy who learned with webquest are higher than who learned without webquest; and (4) on the group with lower level self-ef cacy, student’s knowledge literacy who learned with webquest are lower than who learned without webquest.